2020
DOI: 10.1126/scitranslmed.aay0152
|View full text |Cite
|
Sign up to set email alerts
|

PTEN status determines chemosensitivity to proteasome inhibition in cholangiocarcinoma

Abstract: Patient-derived xenografts (PDXs) and PDX-derived cells (PDCs) are useful in preclinical research. We performed a drug screening assay using PDCs and identified proteasome inhibitors as promising drugs for cholangiocarcinoma (CCA) treatment. Furthermore, we determined that phosphate and tensin homology deleted on chromosome ten (PTEN) deficiency promotes protein synthesis and proteasome subunit expression and proteolytic activity, creating a dependency on the proteasome for cancer cell growth and survival. Thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 55 publications
1
32
0
Order By: Relevance
“…( 80 ) Cholangiocarcinoma PMSA5 a Proteasome Repression ChIP, RT-PCR Jiang et al. ( 144 ) Colorectal melanoma CDKN2A b Cell cycle Repression ChIP, RT-PCR Fang et al. ( 126 , 127 ) Abbreviation: ChIP, chromatin immunoprecipitation.…”
Section: Functions Of Bach1 In Cancer Metastasismentioning
confidence: 99%
“…( 80 ) Cholangiocarcinoma PMSA5 a Proteasome Repression ChIP, RT-PCR Jiang et al. ( 144 ) Colorectal melanoma CDKN2A b Cell cycle Repression ChIP, RT-PCR Fang et al. ( 126 , 127 ) Abbreviation: ChIP, chromatin immunoprecipitation.…”
Section: Functions Of Bach1 In Cancer Metastasismentioning
confidence: 99%
“…Therefore, PDX model provides an alternative preclinical model for the discovery of novel treatment regimens for patients with malignant tumors. Recently, Wang et al constructed a cholangiocarcinoma PDX biobank with an engraftment rate of 83.3% (30 of 36) and used these models to reveal the chemosensitivity of proteasome inhibition in cholangiocarcinoma, which further broadened the application in medical research (17). The first report on ICC PDX model was published in 2016 by Giuliana et al, who successfully established and confirmed the histological and genetic similarity between primary tumor and PDX model (18).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, one rejoices in surprise realizing that PNO1 de cient caused a signi cant increase in protein levels of PTEN and p53 in vivo. A previous study reported that PTEN inhibited proteasome activity and attenuated bortezomib e cacy in CHOL [39]. PTEN might modulate the function of proteasomes [40].…”
Section: Discussionmentioning
confidence: 96%
“…In addition, co-IP analysis indicated that PNO1 knockdown increased the binding of p53 to PTEN ( Figure 6B). It has been reported that PTEN attenuated bortezomib e cacy in CHOL treatment [17]. To explore the effect of manipulating PNO1 abundance on sensitivity to bortezomib, cell models in vitro and PDXs models in vivo were established.…”
Section: Pno1 Facilitates the Therapeutic Effect Of Bortezomib In Cholmentioning
confidence: 99%